Família vende tudo: a representação da família na publicidade brasileira - Godoy, Rodrigo de (2010)
The objective of this study is to catch the "myth" in action through the representation of the family in some brazilian ads. Its corpus is made up of a selection of ads taken from two nationwide publications, chosen for the diversity and the representativeness of the target audience: Seleções de Reader's Digest and Veja. The theoretical basis comprises two main fronts: Barthes semiology and the concept of myth that it develops, on one side; the history and structure of the bourgeois nuclear family, in an arc that goes from Engels to Philippe Ariès, and the changes in advertising in Brazil, on the other side. We hypothesized that, despite the new roles that men and women now play in brazilian society, with few exceptions, the ads remain stuck to an old family model with its old function distribution. This is consistent with the central assertion of Barthes on the subject of mythological discourse: the "myth" takes the nature by culture and cancels history